2009
DOI: 10.1038/nsmb.1610
|View full text |Cite
|
Sign up to set email alerts
|

Localized thermodynamic coupling between hydrogen bonding and microenvironment polarity substantially stabilizes proteins

Abstract: The energetic contributions of hydrogen bonding to protein folding are still unclear, despite over 70 years of study. This is due partly to the difficulty of extracting thermodynamic information about specific interactions from protein mutagenesis data, and partly to the context dependence of hydrogen bond strengths. Herein, we test the hypothesis that hydrogen bond strengths depend on the polarity of their microenvironment, with stronger hydrogen bonds forming in non-polar surroundings. Double mutant thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(200 citation statements)
references
References 61 publications
11
187
0
2
Order By: Relevance
“…Most simply, they asked whether a mutation that affects the propensity of a sequence to form an alpha helix, say decreasing this propensity, destabilizes overall folding of the protein by the same amount. This prediction bore out for mutations in exposed residues on the protein, but this simple rule is not followed for a buried side chain, as desolvation and interactions with neighboring residues affect the energetic contribution of these sides chains to folding (51,(64)(65)(66). As noted above, this approach and potential modularity may be more applicable to RNA tertiary structures given their limited packing interfaces and the sparse distribution of tertiary contacts throughout a structure.…”
Section: Discussionmentioning
confidence: 99%
“…Most simply, they asked whether a mutation that affects the propensity of a sequence to form an alpha helix, say decreasing this propensity, destabilizes overall folding of the protein by the same amount. This prediction bore out for mutations in exposed residues on the protein, but this simple rule is not followed for a buried side chain, as desolvation and interactions with neighboring residues affect the energetic contribution of these sides chains to folding (51,(64)(65)(66). As noted above, this approach and potential modularity may be more applicable to RNA tertiary structures given their limited packing interfaces and the sparse distribution of tertiary contacts throughout a structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that electrostatic screening is the main reason for the distinct backbone conformational preferences of amino acid residues in peptides and proteins (53), the nearest neighbor effect (54), and the formation of transient β-strands in unfolded proteins (55). It has also been shown, using amide to ester mutations, that H bonds in the protein interior are stronger than those exposed to solvent (56)(57)(58).…”
Section: Ir Spectroscopy Of Water Molecules In the Neighborhood Of Pumentioning
confidence: 99%
“…6B). The hydrogen bond interactions between the PH domain and EF hand residues involve residues whose side chain donor and acceptor atoms are 3-4 Å apart, significantly weaker in energy than the average hydrogen bond lengths observed in proteins (ϳ1.5-2 Å) (35). Taken together with the absence of electrostatic interactions or water bridges at this interface, we hypothesized that the PH domain is mobile in solution, existing in equilibrium between the conformation observed in crystal structures and an "open" conformation where the PH domain moves so that the residues required for G␤␥ binding become accessible.…”
Section: Rac1 and G␤␥ Bind Distinct Surfaces On Plc-␤-plc-␤2mentioning
confidence: 99%